Association between Hypothyroidism and Herpes Simplex Virus with Interleukin-23 - Sahar H. Al-Hindawi (Journal of Global Pharma Technology, 2020)
Background: Hashimoto’s thyroiditis and Hypothyroidism play a distinct role in the suppression and reactivation of herpes viruses. Herpes simplex virus infections have been assumed as one of the factors that may trigger autoimmune thyroid diseases; however, IL-23 has an important role in the pathogenesis of several inflammatory and autoimmune conditions. Objective: This study aimed to investigate the association between thyroid hormones in hypothyroid state and the Herpes simplex virus status in such patients; besides detecting the role of IL-23 in these cases. Materials and Methods: The present study included 65 Iraqi female hypothyroid patients with age ranged between 26-54 years and 25 healthy controls with age ranged between 25-50 years. Serum samples were collected from the study groups. Levels of thyroid hormones (TSH, T4, and T3) were determined by using automated Chemiluminescence Immunoassay (CLIA) analysis system. The detection of herpes simplex virus IgG and IL-23 levels in the serum samples were determined by an enzyme linked immunosorbent assay (ELISA) kits. Results: The current study results revealed that serum IL-23 and HSV levels are increased significantly (P<0.001) in the hypothyroid patients group as compared with control. There was a significant positive correlation between TSH and (IL-23, HSV); also between IL-23 and HSV (P<0.01). Moreover, there was a significant negative correlations (P<0.01) between IL-23 with (T4, T3) and between HSV with (T4, T3).  Conclusion: The present study pointed to the association between thyroid hormones deficiency in Hashimoto thyroiditis cases and IL-23 levels through disruption of the patient’s immune system; and with Herpes simplex viruse-1by their role in the replication.Keywords: Hashimoto Thyroiditis, Hypothyroidism, Herpes Simplex Virus, IL-23.